Cost-effective synthesis of unsymmetric tetrazines - Hwang, Jiwon; Yoon, Byeongjip; Suh, Sung Eun (Bulletin of the Korean Chemical Society, 2024)
1,2,4,5-Tetrazines serve as versatile two-carbon synthons, essential for synthesizing a variety of (hetero)aromatic compounds. Their specific reactivity with certain dienophiles, without interfering with biochemical processes, makes them ideal for bioorthogonal ligation. Despite their broad utility, current synthetic methods are costly and raise safety concerns, particularly during scale-up. This study introduces safer and more cost-effective synthetic strategies utilizing zinc chloride or boron trifluoride diethyl etherate as catalysts. These alternatives significantly reduce costs and enhance safety, potentially expanding the applicability of tetrazine synthesis across broader research domains.
Keywords: Biochemical process; Cost effective; Dienophiles; Effective synthesis; Formamidines; Lewis Acid; Nitrile; Specific reactivity; Synthons; Tetrazines; formamidine; hydrazine; Lewis acid; nitrile; tetrazine